The Amino Terminal Domain and Modulation of Connexin36 Gap Junction Channels by Intracellular Magnesium Ions - Kraujalis, Tadas; Gudaitis, Lukas; Kraujaliene, Lina; Snipas, Mindaugas; Palacios-Prado, Nicolás; Verselis, Vytas K. (Frontiers in Physiology, 2022)
Electrical synapses in the mammalian CNS are predominantly formed of the connexin36 (Cx36) gap junction (GJ) channel protein. Unique among GJs formed of the Cx gene family, Cx36 GJs possess a high sensitivity to intracellular Mg2+ that can robustly act to modulate the strength of electrical synaptic transmission. Although a putative Mg2+ binding site was previously identified to reside in the aqueous pore in the first extracellular (E1) loop domain, the involvement of the N-terminal (NT) domain in the atypical response of Cx36 GJs to pH was shown to depend on intracellular levels of Mg2+. In this study, we examined the impact of amino acid substitutions in the NT domain on Mg2+ modulation of Cx36 GJs, focusing on positions predicted to line the pore funnel, which constitutes the cytoplasmic entrance of the channel pore. We find that charge substitutions at the 8th, 13th and 18th positions had pronounced effects on Mg2+ sensitivity, particularly at position 13 at which an A13K substitution completely abolished sensitivity to Mg2+. To assess potential mechanisms of Mg2+ action, we constructed and tested a series of mathematical models that took into account gating of the component hemichannels in a Cx36 GJ channel as well as Mg2+ binding to each hemichannel. Simultaneous model fitting of measurements of junctional conductance and transjunctional Mg2+ fluxes using a fluorescent Mg2+ indicator suggested that the most viable mechanism for Cx36 regulation by Mg2+ entails the binding of Mg2+ to and subsequent stabilization of the closed state in each hemichannel. Reduced permeability to Mg2+ was also evident, particularly for the A13K substitution, but homology modeling of all charge-substituted NT variants showed only a moderate correlation between a reduction in the negative electrostatic potential and a reduction in the permeability to Mg2+ ions. Given the reported role of the E1 domain in Mg2+ binding together with the impact of NT substitutions on gating and the apparent state-dependence of Mg2+ binding, this study suggests that the NT domain can be an integral part of Mg2+ modulation of Cx36 GJs likely through the coupling of conformational changes between NT and E1 domains.